Transnational migration of health professionals in the European Union Migração transnacional de profissionais de saúde na União Européia - Thomas Gerlinger; Rolf Schmucker (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The establishment of the European Common Market has involved the free movement not only of capital and goods, but also of persons and services. The principles of free movement also apply to the health care sector, i.e. they allow for the free incorporation of health care providers and the cross-border delivery of services. Since the 1970s, the European Union (EU) has passed numerous regulations to enforce the mutual recognition of qualifications of physicians, nurses, and other health professionals by the Member States, considered an indispensable precondition for the free movement of services. Thus far, the establishment of a European job market for the health care professions has not led to extensive migration among the EU Member States. Likewise, the accession of Central and Eastern European countries to the EU in 2004 did not cause a "brain drain" to the better-off countries of Western and Northern Europe. However, the mobility among health care professions is expected to increase in the coming years. A criação do Mercado Comum Europeu envolve a circulação livre tanto de capital e produtos quanto de pessoas e serviços. Os princípios da circulação livre se aplicam igualmente ao setor de saúde, i.e., permitem a incorporação livre de provedores de assistência e a prestação transfronteiriça dos serviços. Desde os anos 70, a União Européia (UE) tem aprovado várias normas voltadas para o reconhecimento recíproco da qualificação de médicos, enfermeiros e outros profissionais de saúde pelos Países Membros, como pré-condição indispensável para a movimentação livre de serviços. Até o momento, a criação de um mercado de trabalho europeu para as profissões de saúde não levou a uma migração extensa entre os Países Membros. A entrada de países do Leste Europeu e Europa Central para a UE tampouco provocou uma "fuga de cérebros" aos países mais abastados do Oeste e Norte do continente. Entretanto, a previsão é de que a mobilidade entre as profissões de saúde deve aumentar na Europa nos próximos anos.